The Analysis of The Effect of Profitability and Other Factors on Earnings Management - Livani Arta Hiudy; Indra Arifin Djashan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The objective of this research is to obtain empirical evidence of independent variables related to earnings management in non-financial companies. The independent variables used in this research are managerial ownership, institutional ownership, firm size, leverage, return on assets, sales growth, board size, and audit committee. This research used companies listed in non-financial sectors in Indonesia Stock Exchange from 2019 until 2021. There are 321 sample datas selected by using purposive sampling method. The model used in this research is multiple regression analysis. The result of this research shows that return on assets has an effect on earnings management. On the other hand, other independent variables, such as, managerial ownership, institutional ownership, firm size, leverage, sales growth, board size, and audit committee have no effect on earnings management.